Impact of axis misalignment of toric intraocular lenses on refractive outcomes after cataract surgery - Jin, Haiying; Limberger, Il-Joo; Ehmer, Angela; Guo, Haike; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2010)
PURPOSE: - To theoretically and clinically evaluate the impact of axis misalignment of toric intraocular lenses (IOLs) on postoperative refraction. - SETTING: - International Vision Correction Research Center, University of Heidelberg, Heidelberg, Germany. - DESIGN: - Case series. - METHODS: - A method based on mathematical solutions to obliquely crossed spherocylinders was derived according to the pseudophakic refractive properties and used to analyze the impact of toric IOL misalignment on postoperative refraction. The refractive outcomes were theoretically analyzed and actual postoperative outcomes assessed to confirm the theoretically identified impact. - RESULTS: - The mean IOL misalignment was 12.5 degrees ± 6.7 (SD). Three main factors had an impact on refractive outcomes: hyperopic change in refractive sphere, reduction in astigmatic correction, and rotation of the astigmatic axis. The mean calculated spherical change was 0.32 ± 0.23 diopters (D) and the actual change, 0.36 ± 0.71 D. The mean calculated reduction in astigmatic correction was 0.65 ± 0.45 D and the actual reduction, 0.95 ± 0.54 D, indicating undercorrection of preexisting astigmatism. The mean calculated absolute astigmatic rotation was 32.7 ± 13.2 degrees (range 8 to 55 degrees) and the actual rotation, 29.1 ± 17.4 degrees. There was a correlation between the calculated and actual reduction (r2 = 0.51; P = .001) and between the calculated and actual rotation (r2 = 0.86; P<.001). - CONCLUSION: - In addition to a reduction in astigmatic correction, misalignment of toric IOLs induced hyperopic spherical change and astigmatic rotation. - Financial Disclosure: - No author has a financial or proprietary interest in any material or method mentioned.